2011
DOI: 10.1111/j.1365-2036.2011.04728.x
|View full text |Cite
|
Sign up to set email alerts
|

High resolution manometry to detect transient lower oesophageal sphincter relaxations: diagnostic accuracy compared with perfused‐sleeve manometry, and the definition of new detection criteria

Abstract: High resolution manometry is reproducible and more sensitive than PSM to detect tLESRs. HRM provides a better interobserver agreement. These results confirm that HRM is the gold standard for detecting tLESRs (NTC00931593).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 23 publications
3
50
1
2
Order By: Relevance
“…Specifically, the study aimed to identify motor dysfunctions not diagnosed by conventional manometry or radiology [12], using a series of closely spaced pressure sensors to simultaneously view the entire swallowing mechanism, with a speci c focus on LES motility [13]. is approach permits a more detailed analysis of motor function than has previously been undertaken in these individuals [12,[14][15][16]]. An additional aim was to evaluate whether changes in body position or bolus J Gastrointestin Liver Dis, September 2014 Vol.…”
mentioning
confidence: 99%
“…Specifically, the study aimed to identify motor dysfunctions not diagnosed by conventional manometry or radiology [12], using a series of closely spaced pressure sensors to simultaneously view the entire swallowing mechanism, with a speci c focus on LES motility [13]. is approach permits a more detailed analysis of motor function than has previously been undertaken in these individuals [12,[14][15][16]]. An additional aim was to evaluate whether changes in body position or bolus J Gastrointestin Liver Dis, September 2014 Vol.…”
mentioning
confidence: 99%
“…Indeed, HRM improves characterization of LES zones and esophageal body motility, increasing diagnostic yield and accuracy [121] . Moreover, HRM must be regarded as the new gold standard for detecting TLESRs [43] . However, the value of HRM in clinical practice has yet to be established fully Exclusion of severe esophageal motility disorders (i.e., achalasia) is important because such diseases can present with heartburn and regurgitation, which could lead to an erroneous diagnosis of GERD [122] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, minor but they are accompanied by diaphragmatic inhibition, and they persist for longer periods than swallowinduced LES relaxations (> 10 s) [41,42] . In a recent study, Roman et al [43] demonstrated that HRM is reproducible and more sensitive than perfused-sleeve manometry to detect TLESRs, providing better interobserver agreement. Notably, in GERD patients, there is not an increased frequency of TLESR compared with controls but only a greater frequency of acid reflux during TLESRs [44] .…”
Section: High Resolution Manometrymentioning
confidence: 99%
“…Kuribayashi et al [14] reported that the Starlet with a Unisensor catheter could evaluate esophageal motility precisely. TLESRs were evaluated according to previously published criteria for HRM reported by Roman et al [15], as follows: (1) absence of swallowing for 4 s before and for 2 s after the onset of LES relaxation; (2) the 4-s integrated relaxation pressure measured within the LES relaxation was 50% or less of the basal LES pressure; (3) the presence of swallowing was allowed if the LES relaxation duration was longer than 10 s in the absence of multiple swallows; and (4) inhibition of the crural diaphragm was also taken into account (fig. 1a).…”
Section: Methodsmentioning
confidence: 99%